Α‐Synuclein aggregation causes muscle atrophy through neuromuscular junction degeneration. Issue 1 (23rd November 2022) - Yang, Qiumei; Wang, Yanyan; Zhao, Chunsong; Pang, Shimin; Lu, Jing; Chan, Piu
Abstract: Background: Sarcopenia is common in patients with Parkinson's disease (PD), showing mitochondrial oxidative stress in skeletal muscle. The aggregation of α‐synuclein (α‐Syn) to induce oxidative stress is a key pathogenic process of PD; nevertheless, we know little about its potential role in regulating peripheral nerves and the function of the muscles they innervate. Methods: To investigate the role of α‐Syn aggregation on neuromuscular system, we used the Thy1 promoter to overexpress human α‐Syn transgenic mice (mThy1‐hSNCA). hα‐Syn expression was evaluated by western blot, and its localization was determined by confocal microscopy. The impact of α‐Syn aggregation on the structure and function of skeletal muscle mitochondria and neuromuscular junctions (NMJs), as well as muscle mass and function were characterized by flow cytometry, transmission electron microscopy, Seahorse XF24 metabolic assay, and AAV9 in vivo injection. We assessed the regenerative effect of mitochondrial‐targeted superoxide dismutase (Mito‐TEMPO) after skeletal muscle injury in mThy1‐hSNCA mice. Results: Overexpressed hα‐Syn protein localized in motor neuron axons and NMJs in muscle and formed aggregates. α‐Syn aggregation increased the number of abnormal mitochondrial in the intramuscular axons and NMJs by over 60% ( P  < 0.01), which inhibited the release of acetylcholine (ACh) from presynaptic vesicles in NMJs ( P  < 0.05). The expression of genes associated with NMJ activity, neurotransmission and regulation of reactive oxygen species (ROS) metabolic process were significantly decreased in mThy1‐hSNCA mice, resulting in ROS production elevated by ~220% ( P  < 0.05), thereby exacerbating oxidative stress. Such process altered mitochondrial spatial relationships to sarcomeric structures, decreased Z‐line spacing by 36% ( P  < 0.05) and increased myofibre apoptosis by ~10% ( P  < 0.05). Overexpression of α‐Syn altered the metabolic profile of muscle satellite cells (MuSCs), including basal respiratory capacity (~170% reduction) and glycolytic capacity (~150% reduction) ( P  < 0.05) and decreased cell migration and fusion during muscle regeneration (~60% and ~40%, respectively) ( P  < 0.05). We demonstrated that Mito‐TEMPO treatment could restore the oxidative stress status (the complex I/V protein and enzyme activities increased ~200% and ~150%, respectively), which caused by α‐Syn aggregation, and improve the ability of muscle regeneration after injury. In addition, the NMJ receptor fragmentation and ACh secretion were also improved. Conclusions: These results reveal that the α‐synuclein aggregation plays an important role in regulating acetylcholine release from neuromuscular junctions and induces intramuscular mitochondrial oxidative stress, which can provide new insights into the aetiology of muscle atrophy in patients with Parkinson's disease.